Repositioning of the Severe Prolapsed Silicone Tubes after Bicanalicular Nasal Intubation: A Novel Technique - Jinjing He; Jingwen Gong; Qingqing Zheng; Jin Jiang (Journal of Ophthalmology)
Background. Bicanalicular nasal intubation is widely used in lacrimal drainage system surgery. Its common complication is lateral displacement or spontaneous prolapse. When the distal part of the silicone tubes cannot be seen in the nose endoscopically, either repositioning or removal could be a challenge. We developed a simple technique to reposition the severe prolapsed silicone tubes. Method. This retrospective study included 6 patients with severe prolapsed silicone tubes who had undergone bicanalicular nasal intubation between January 2017 and December 2019. We used a memory wire probe to pull a nylon suture through the lacrimal passage retrograde. Then, the nylon suture was cut into two lines. One line was coiled to the prolapsed tube and tied to another line. This nylon turned into a “lasso” to capture the silicone tube and then lock its knot. By pulling the nylon suture, the severe prolapsed silicone tube was repositioned to the nasal cavity. Results. Using this technique, we successfully repositioned severe prolapsed silicone tubes without any complication in 6 cases. Conclusions. Silicone tube reposition guiding by using a memory wire probe is an optional technique in the treatment of prolapse of silicone tubes, particularly if the distal part of the silicon tube was embedded in the lacrimal sac and cannot be seen in the nose by endoscopy. It is a feasible, minimally invasive, safe, and effective method, avoiding premature tube removal.